2016
DOI: 10.1002/poc.3588
|View full text |Cite
|
Sign up to set email alerts
|

Solvent network at the transition state in the solvolysis of hindered sulfonyl compounds

Abstract: Alcoholysis rates of unhindered benzenesulfonyl chlorides (X‐ArSO2Cl, X = H‐; 4‐Br‐; 4‐Me‐) are similar in methanol; the same behavior is also observed in ethanol, whereas the reactivity order in iso‐propanol is 4 Me‐ < H‐ < 4‐Br‐. On the other hand, alcoholysis of sterically hindered arenesulfonyl chlorides (X‐ArSO2Cl) (X = 2,4,6‐Me3‐3‐NO2‐; 2,6‐Me2‐4‐tBu‐; 2,4,6‐Me3‐; 2,3,5,6‐Me4‐; 2,4,6‐iPr3‐; 2,4‐Me2‐; 2,4,6‐(OMe)3‐) in all studied alcohols show a significant increase in reactivity, the so‐called positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Later on, the increased reactivity of ortho-alkyl substituted benzenesulfonyl chlorides, defined as "steric acceleration", was claimed to be due to relief of strain in the transition state having trigonal bipyramidal structure [40]. More recently, it was proposed that the structure of reactants and molecularity of the transition state with nucleophilic assistance of solvent may be responsible for the increased reactivity of hindered sulfonyl chlorides [13].…”
Section: Kinetics Of Isotopic Chloride-chloride Exchange Reaction In mentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, the increased reactivity of ortho-alkyl substituted benzenesulfonyl chlorides, defined as "steric acceleration", was claimed to be due to relief of strain in the transition state having trigonal bipyramidal structure [40]. More recently, it was proposed that the structure of reactants and molecularity of the transition state with nucleophilic assistance of solvent may be responsible for the increased reactivity of hindered sulfonyl chlorides [13].…”
Section: Kinetics Of Isotopic Chloride-chloride Exchange Reaction In mentioning
confidence: 99%
“…With regard to the sulfonyl transfer reactions, The results of very extensive kinetic studies on the nucleophilic substitution reactions at the sulfonyl center and mechanistic conclusions drawn from them have been summarized in an excellent review paper entitled "Sulfonyl Transfer Reactions" published in 1989 [12]. This direction of kinetic investigations is continued until recently with a various intensity [13,14]. Generally, the substitution reactions at the sulfonyl sulfur are discussed in term of the concerted S N 2-type displacement involving a single transition state which may be tighter or looser depending on the substituents present.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the rate constants used in this correlation are taken from ref . The full set of data is available as a Table S8 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…From Tables and , and published research, it follows that not only electronic effects play a role in the alcoholysis of arenesulfonyl chlorides . Although no Hammett correlations have been found, there is a tendency for the reactivity to increase with the number of alkyl substituents (Tables and Figures and ), but at the same time, the reaction rate of non‐ ortho ‐alkylated substrates is reduced by 30% when H‐ or Me‐ is replaced by t ‐butyl in para‐ position (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that, in addition to having an alcohol or water as the attacking nucleophile with a second alcohol of water as a general base, one can proceed in an alcoholysis reaction through a cyclic structure involving three molecules of the alcohol and the sulfur of the sulfonyl chloride present in the ring [ 52 ]. One would predict that such an extremely ordered pathway would have a very negative entropy of activation, but the required studies with temperature variation to investigate this aspect were not reported.…”
Section: Reviewmentioning
confidence: 99%